Fabrication of highly expanded thermoplastic polyurethane foams using microcellular injection molding and gas‐laden pellets. Issue 11 (11th August 2015) - Sun, Xiaofei; Kharbas, Hrishikesh; Turng, Lih‐Sheng
<x xml:space="preserve">Abstract</x> Thermoplastic polyurethane (TPU) is one of the most widely used and versatile thermoplastic materials. TPU foams have been extensively applied in various industries including the furniture, automotive, sportswear, and packaging industries. In this study, two methods of producing highly expanded TPU injection molded foam were investigated: (1) microcellular injection molding (MIM) with N2 as a blowing agent, and (2) a novel gas‐laden pellet/MIM combined process with N2 and CO2 as co‐blowing agents. Two designs of experiments (DOEs) were performed to learn the influences of key processing parameters and to optimize foam quality. By using N2 and CO2 as co‐blowing agents, a bulk density as low as 0.20 g/cm3 was successfully achieved with a hysteresis compression loss of 24.4%. POLYM. ENG. SCI., 55:2643–2652, 2015. © 2015 Society of Plastics Engineers